Mean response latency indices on the Victoria Symptom Validity Test do not contribute meaningful predictive value over accuracy scores for detecting invalid performance. Issue 6 (2nd November 2022) - Cerny, Brian M.; Rhoads, Tasha; Leib, Sophie I.; Jennette, Kyle J.; Basurto, Karen S.; Durkin, Nicole M.; Ovsiew, Gabriel P.; Resch, Zachary J.; Soble, Jason R.
Abstract: The utility of the Victoria Symptom Validity Test (VSVT) as a performance validity test (PVT) has been primarily established using response accuracy scores. However, the degree to which response latency may contribute to accurate classification of performance invalidity over and above accuracy scores remains understudied. Therefore, this study investigated whether combining VSVT accuracy and response latency scores would increase predictive utility beyond use of accuracy scores alone. Data from a mixed clinical sample of 163 patients, who were administered the VSVT as part of a larger neuropsychological battery, were analyzed. At least four independent criterion PVTs were used to establish validity groups (121 valid/42 invalid). Logistic regression models examining each difficulty level revealed that all VSVT measures were useful in classifying validity groups, both independently and when combined. Individual predictor classification accuracy ranged from 77.9 to 81.6%, indicating acceptable to excellent discriminability across the validity indices. The results of this study support the value of both accuracy and latency scores on the VSVT to identify performance invalidity, although the accuracy scores had superior classification statistics compared to response latency, and mean latency indices provided no unique benefit for classification accuracy beyond dimensional accuracy scores alone.